SOSIALISASI PENDAMPINGAN BELAJAR ANAK DI MASA PANDEMI COVID-19 - Winia Waziana (Jurnal PkM Pemberdayaan Masyarakat, 2022)
Parents are the main aspect in the process of education and child development. Meanwhile, the world of education must adapt to changes that occur as a result of the Covid-19 pandemic, because learning today is different from before. Learning that is usually face-to-face has been replaced with online or online learning. Therefore, the role of parents is very important in assisting children in doing tasks online. Many parents do not understand how to accompany their children to study properly, and what applications are used during online lessons, so the researchers held socialization for parents with the title "Children's Learning Assistance during the Covid-19 Pandemic". The goal is to provide an understanding of good and correct child learning assistance so that learning can run as expected. The socialization event received a good response from parents for the socialization activities carried out by the students of the STMIK Pringsewu PkM Team.